JUDICIALIZAÇÃO, SAÚDE E JUSTIÇA: uma análise a partir do Hospital Universitário da Universidade Federal do Maranhão (HUUFMA) no período de 2014 a 2019. - ALMEIDA, Natalie Maria de Oliveira de (2020)
Public health is a topic that requires a lot of attention, as it is a social problem while it is also an obligation of the State. However, its implementation meets several obstacles of an economic, social and even natural order, which makes the subject extremely complex. As a consequence, society understands this situation as a failure derived from the omission of the Public Power and has sought to remedy it, frequently, through requests regarding health before the Judiciary. In general, this phenomenon is defined by judicialization. Based on the assumption that Maranhão has suffered strong impacts due to this high number of demands, the objective of this research was to analyze access to health at HUUFMA, through requests referring to surgeries for adult men and women in the period from 2014 to 2019, from the perspective of Rawlsian theory of justice, proposing health mediation as an instrument of consensual justice capable of adequately responding to demands.